Comparative Life Cycle Assessment of the hull of a high-speed craft. (May 2016) - Burman, Magnus; Kuttenkeuler, Jakob; Stenius, Ivan; Garme, Karl; Rosén, Anders
A comparative Life Cycle Assessment is performed for different structural material concepts on a 24-m-long high-speed patrol craft. The study is comparative and determines the differences in and sensitivities to environmental impact, especially in relation to the total impact of fuel burn for the different material concepts. The material concepts are aluminium and various composite combinations consisting of glass fibre and carbon fibre with vinyl ester resin both as single skins and as sandwich with a Divinycell foam core. Commercially available standard Life Cycle Assessment software is used for the Life Cycle Assessment calculations. The study shows that regardless of hull material concept, the environmental impact is dominated by the operational phase due to relatively large fuel consumption. In the operational phase, the lightest carbon-fibre concept is shown to have least environmental impact. Considering the manufacturing phase exclusively for the different hull concepts, it is concluded that the manufacturing of the aluminium hull has a somewhat larger environment impact for the majority of Life Cycle Assessment impact categories in comparison to the different composite hulls. The significant impact on the marine and the fresh water aquatic ecotoxicity originates from the aluminium raw material excavation and manufacturing processes. It is shown that the lightest hull, the carbon-fibre sandwich concept, with a 50% structural weight reduction compared to the aluminium design, can be utilized to reduce the fuel consumption by 20% (775 ton of diesel) over the lifetime with significant impact on the dominating environmental aspects considered herein, abiotic depletion, global warming and acidification.